1999
DOI: 10.1023/a:1020533318323
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: During the 6-year period (January 1, 1993 to December 31, 1998) in the Laboratory for Dermatopathology of Department of Dermatovenereology in Clinical Hospital Split, 1616 basal cell carcinomas (BCC) of a total of 323 investigated specimens were diagnosed. The incident rate varies from 92 to 114 BCC per 100,000 inhabitants in the Split region. The sex ratio in material is 1.2:1 in favor of males. The frequence of BCC increases with the advanced age in both sexes with the peak in the age group from 70 to 79 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Weedon [3] and Haws and colleagues [27] opined that the mixed type is most frequently seen, but a study showed that the solid variant is most frequently seen [28], and superficial multicentric and solid-adenoid variants were observed. Puizina-Ivić and colleagues observed pure and mixed variants at a rate of 83.1% and 16.9%, respectively [28]. Nakjang and Kullavanijaya [29] opined that pigmentation was most frequently seen in solid, superficial and adenoid subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Weedon [3] and Haws and colleagues [27] opined that the mixed type is most frequently seen, but a study showed that the solid variant is most frequently seen [28], and superficial multicentric and solid-adenoid variants were observed. Puizina-Ivić and colleagues observed pure and mixed variants at a rate of 83.1% and 16.9%, respectively [28]. Nakjang and Kullavanijaya [29] opined that pigmentation was most frequently seen in solid, superficial and adenoid subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-ageing skin care treatments range from cosmetic preparations, fillers and neurotoxins, to surgical intervention and laser skin resurfacing [46,47]. However, adverse effects have been associated with many of these methods, and the desire for safe and effective products that reduce wrinkles and improve skin elasticity remains high.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is associated with several dermatologic conditions, including psoriasis, wound healing, premature skin ageing, squamous cell carcinoma, melanoma, oral cancer, acne, eczema and hair loss (12). Findings from a recent research study clearly demonstrated that tobacco smoking is another environmental factor contributing to premature ageing (13). 'Smoker's face' and 'cigarette skin', meaning increased facial wrinkling and an ashen and grey skin appearance, are characteristic (14).…”
Section: Discussionmentioning
confidence: 99%